ANALISIS FAKTOR YANG MEMPENGARUHI TRANSFER PRICING ANTAR PERUSAHAAN KONSOLIDASI DI INDONESIA - Amalia Nessa Arlinda; Ayuk Yuliana; Endang Kartini Panggiarti (Melati Institute, 2023)
The development of national companies into international ones raises the potential for transfer pricing which can reduce state tax revenues. This study aims to describe aspects of transfer pricing from an accounting and tax perspective, the factors that most influence the consolidated company's decision to practice transfer pricing, and how to minimize the risk of loss of state revenue as a result of transfer pricing practices. Qualitative research with the type of descriptive statistical research and secondary data types obtained from various collections of articles through the Google Scholar page using the keyword